Global trends in intestinal flora and ulcerative colitis research during the past 10 years: A bibliometric analysis - Zhang, Lu; Xiong, Shuai; Jin, Fengchen; Zhou, Fan; Zhou, Hongjun; Guo, Jinhong; Wen, Chuanbiao; Huang, Biao (Frontiers in Microbiology, 2022)
Background and Aim: Ulcerative colitis is a chronic inflammatory bowel disease, and intestinal flora plays an important role in ulcerative colitis. In this study, we conducted a bibliometric analysis of publications in the field of intestinal flora and ulcerative colitis research in the past 10 years to summarize the current status of the field and analyze the trends in the field. Methods: On July 15, 2022, we chose the Web of Science Core Collection database as the study's data source. Citespace.5.8.R3 and Vosviewer1.6.17 were used to examine publications of research on intestinal flora and ulcerative colitis that were published between 2012 and 2021. We looked through the papers for journals, organizations, nations and regions, authors, and key terms. Results: This analysis covered a total of 2763 papers on studies into intestinal flora and ulcerative colitis. There were 13913 authors, 93 nations, 3069 organizations, and 759 journals in all of the articles. In the United States, 767 publications were the most. The university with the most publications was Harvard Medical School. The author with the most articles was Antonio Gasbarrini. Conclusion: This study summarizes the global research trends in intestinal flora and ulcerative colitis. Publications in this field have increased year by year in the last decade and the field of research on intestinal flora and ulcerative colitis has good prospects for growth.